Counseling in Turkey: Current Status and Future Challenges - Dogan, Suleyman (Education Policy Analysis Archives, 1998)
In this article a special emphasis is placed on the current status and the future challenges of counseling in Turkey. A brief history of counseling in Turkey, current developments, and the basic issues in this field are pointed out. Finally, the future challenges and recommendations to improve the current status of counseling are discussed.